Analisis Retensi Pelanggan dan Switching Costs terhadap Loyalitas Pelanggan Indihome - Dwi Sri Wahyuni; Erry Sunarya; Nor Norisanti (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine the effect of customer retention and switching costs simultaneously on the loyalty of Indihome customers at Witel Sukabumi. This research method is descriptive quantitative. The data analysis technique used in this study was multiple correlation, coefficient of determination (R2), multiple linear regression analysis technique and F. The results showed, Adjusted R Square was 0.465 (46.5%). This means that the variation of customer loyalty can be explained by the second independent variable, namely customer retention and switching costs, while the remaining 53.5% (100%-46.5% = 53.5%) is another factor outside the study. In conclusion, customer retention and switching costs have a positive and significant effect on customer loyalty simultaneously. Keywords: Customer Loyalty, Customer Retention, Switching Costs